1992
DOI: 10.21273/jashs.117.1.174
|View full text |Cite
|
Sign up to set email alerts
|

Gene Transfer Using Electric Discharge Particle Bombardment and Recovery of Transformed Cranberry Plants

Abstract: Genetic transformation of the American cranberry, Vaccinium macrocarpon Ait., was accomplished using electric discharge particle acceleration. Plasmid DNA containing the genes GUS (β-glucuronidase), NPTII (neomycin phosphotransferase II), and BT (Bacillus thuringiensis subsp. kurstaki crystal protein) was introduced into stem sections, derived from in vitro cultures, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 20 publications
(23 reference statements)
0
26
0
Order By: Relevance
“…Recombinant DNA and transformation techniques have been reported that can supplement and extend conventional breeding methods for cranberry (Serres et al 1992(Serres et al , 1997Polashock and Vorsa 2002a;Zeldin et al 2002) and blueberry (Graham et al 1996;Song and Sink 2004;Song et al 2008). While transgenic breeding can play an important role in introducing desirable agronomic traits not possible by conventional breeding into commercial Vaccinium varieties, it is obvious that reliable, efficient transformation protocols must first be developed (Polashock and Vorsa 2002a;McCown and Zeldin 2005;Rowland and Hammerschlag 2005;Hancock et al 2008b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant DNA and transformation techniques have been reported that can supplement and extend conventional breeding methods for cranberry (Serres et al 1992(Serres et al , 1997Polashock and Vorsa 2002a;Zeldin et al 2002) and blueberry (Graham et al 1996;Song and Sink 2004;Song et al 2008). While transgenic breeding can play an important role in introducing desirable agronomic traits not possible by conventional breeding into commercial Vaccinium varieties, it is obvious that reliable, efficient transformation protocols must first be developed (Polashock and Vorsa 2002a;McCown and Zeldin 2005;Rowland and Hammerschlag 2005;Hancock et al 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…(Nickerson and Hall 1976;Nickerson 1978Nickerson , 1980Dweikat and Lyrene 1988), highbush blueberry (V. corymbosum L.) (Billings et al 1988;Callow et al 1989;Ogden 1992, 1993;Hruskoci and Read 1993;Cao and Hammerschlag 2000;Song and Sink 2004), large cranberry (V. macrocarpon Ait.) (Serres et al 1992(Serres et al , 1997Marcotrigiano et al 1996;Qu et al 2000), lingonberry (V. vitis-idaea L.) (Debnath and McRae 2002;Debnath 2005;Meiners et al 2007), and bilberry (V. myrtillus L.) (Shibli and Smith 1996). Most of the regeneration occurred via organogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…), however, there has been only one report of the use of tissue culture to induce adventitious shoots. Serres et al (1992) regenerated shoots from internode segments of micropropagated shoots as a part of a gene transfer protocol using particle bombardment. The efficiency and reproducibility of the system was not reported.…”
Section: Introductionmentioning
confidence: 99%
“…was accomplished via electric discharge particle bombardment (Serres et al ., 1992) . Stem sections derived from in vitro cultures 23 were bombarded with gus, npt II and bt genes.…”
Section: Cotton (Gossypium Hirsutum)mentioning
confidence: 99%